Key Management Skills for Integral Civil Engineering Education - Gómez, Miguel Ángel; Herrera, Rodrigo Fernando; Atencio, Edison; Munoz-La Rivera, Felipe Cristóbal (International Journal of Engineering Pedagogy (iJEP), 2021)
Architecture, Engineering and Construction (AEC) industry requires many interactions between professionals of different areas. Thus, project managers in the AEC industry should have a set of management-aligned skills. International agreements and accreditation boards states the expected skills for engineering graduates, but they usually overrate technical skills. This study aims to identify the most relevant skills in management for civil engineer's education. To achieve this, a literature review was carried out and a list of 129 competencies was obtained. This list was summarized in 34 competencies, and his importance level was evaluated using a web-based survey, targeted to Chilean project managers and civil engineers. The collected skills were classified in management, technical and soft skills. According to respondents, the 34 skills described in this paper are important for the exercise of the profession. However, the most important skills in relative terms are soft skills, then management, and finally, technical skills.